2019
DOI: 10.3748/wjg.v25.i31.4437
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis in cirrhosis: Why a well-known complication is still matter of debate

Abstract: Portal vein thrombosis (PVT) represents a well-known complication during the natural course of liver cirrhosis (LC), ranging from asymptomatic cases to life-threating conditions related to portal hypertension and hepatic decompensation. Portal flow stasis, complex acquired hypercoagulable disorders and exogenous factors leading to endothelial dysfunction have emerged as key factors for PVT development. However, PVT occurrence remains unpredictable and many issues regarding its natural history, prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 97 publications
(137 reference statements)
0
65
0
2
Order By: Relevance
“…11 The indication, contraindication, and currently available therapeutic agents are summarized in Supplementary Table 3. [1][2][3]11,25,46,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Anticoagulation Anticoagulation is the primary management of acute PVT, with supporting evidence of high efficacy and a favorable safety profile ( Table 1). The objective is to achieve recanalization of the portal vein and prevent the extension of the thrombus to decrease the notorious consequences of portal hypertension and mesenteric ischemia and allow conventional end-to-end portal vein anastomosis to be technically possible in transplant candidates.…”
Section: Managementmentioning
confidence: 99%
“…11 The indication, contraindication, and currently available therapeutic agents are summarized in Supplementary Table 3. [1][2][3]11,25,46,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Anticoagulation Anticoagulation is the primary management of acute PVT, with supporting evidence of high efficacy and a favorable safety profile ( Table 1). The objective is to achieve recanalization of the portal vein and prevent the extension of the thrombus to decrease the notorious consequences of portal hypertension and mesenteric ischemia and allow conventional end-to-end portal vein anastomosis to be technically possible in transplant candidates.…”
Section: Managementmentioning
confidence: 99%
“…Based on the current available data, the incidence of PVT in cirrhotic patients is higher than that in noncirrhotic population, varying from 10% to 15% ( 1 ). PVT aggravates the complications of portal hypertension ( 2 , 3 ), and occlusive PVT decreases the post-transplantation survival rate ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological studies on cirrhotic livers have shown that micro-thrombotic occlusion of small intrahepatic veins and sinusoids, secondary to hepatic necroinflammation, frequently occurs; this event is followed by progressive venous obstruction and enhanced fibrogenesis through a process called parenchymal extinction, which may eventually lead to liver dysfunction, worsening of portal hypertension and PVT [ 58 60 ]. A pathogenic model of NASH progression has been proposed based on lipotoxic necrotic damage, leading to direct inflammatory injury of hepatic veins and, finally, venous obstruction with secondary collapse, fibrous septation and cirrhosis [ 61 ].…”
Section: Thromboembolism In Liver Diseasesmentioning
confidence: 99%